La Güera Rodríguez: la construcción de una leyenda - Arrom, Silvia Marina (El Colegio de México, A.C., 2019)
María Ignacia Rodríguez de Velasco, known simply as La Güera Rodríguez, has fascinated Mexicans both during her life and posthumously. This article compares the “real” woman with her later historical, literary and artistic representations. It follows her life story (which is interesting, but not extraordinary for a woman of her class and times), her disappearance from Mexican literature during the second half of the 19th Century and her resurrection and transformation into an iconic figure in the 20th and 21st centuries. In this long road to fame, her image got further and further from the flesh-and-blood woman who lived from 1778 to 1850. There are so many myths surrounding her that it’s difficult to separate the woman from the legend. This analysis of the construction of these legends illuminates Mexican culture during many periods, because the different versions of La Güera that have been developed at different times reflect the ideology of each author and the context of their times. It also reminds us that history is living and that there is a great gulf between historic events and their memory.